Perbandingan Novel Raise the Red Lantern Karya Su Tong dan Film Raise the Red Lantern Karya Zhang Yimou dengan Pendekatan Ekranisasi - Ambar Widiawati; Tri Budianingsih; Sri Hartati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
Raise the Red Lantern is one of Zhang Yimou's films adapted from Su Tong's Raise the Red Lantern novel. This novel and film tells the story of polygamy in Chinese society in the 1920s. Tells the story of the competition of 4 wives in fighting over the love and power of a wealthy master. The shift from the novel Raise the Red Lantern to the film Raise the Red Lantern causes the deletion, addition, and various changes in the intrinsic elements of the novel. These aspects are analyzed from data in the form of novels and films using the ecranisation approach. The goal is to find out the differences, similarities, and changes that occur as a result of the process of transferring vehicles from these two different material objects. The results of the analysis of the ecranisation of the novel Raise the Red Lantern into the film Raise the Red Lantern show that there are additions and deletions of events, alterations and deletions of settings, as well as replacement and removal of characters in the novel. However, the process of transferring vehicle does not change the outline of the story.Keywords - novel, film, raise the Red Lantern, ecranisation.